PERANCANGAN PENGEMBANGAN ARSITEKTUR SISTEM INFORMASI AKADEMIK DENGAN MENGGUNAKAN TOGAF (STUDI KASUS : STMIK AMIKOM PURWOKERTO - Rahman Rosyidi; Purwadi Purwadi (Telematika, 2014)
The main problem as a part of a college education and teaching that many users are connected with the service . In addition to requiring accurate information in the data processing , information systems that exist in academic also used to facilitate student . By analyzing performance information system is used, it can be seen that the management of the organization's performance is good or not . This proposal entitled " Design Development Academic Information System Architecture Using TOGAF Case Study : STMIK Amikom Navan " . The purpose of this study is to investigate and analyze the design of enterprise architecture models of academic information system using the TOGAF ADM in STMIK Amikom Purwokerto . The research used a case study , the research objectives of academic information system at STMIK Amikom Purwokerto . This study will outline the academic information system architecture model of using TOGAF